2021
DOI: 10.20524/aog.2021.0660
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional deficiencies and predictors of mortality in diabetic and nondiabetic gastroparesis

Abstract: Background Gastroparesis is a debilitating condition that may impact morbidity and mortality, but there is a lack of long-term studies examining this relation. The aim of this study was to determine the predictors of mortality in gastroparesis and to determine the nutritional deficiencies. Methods Between September 30, 2009 and January 31, 2020, we identified 320 patients (mean age 47.5±5.3 years, 70% female, 71.3% Whites, 39.7% diabetic and 60.3% nondiabetic) with gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
4
1
1
Order By: Relevance
“…In the current study, the frequency of vitamin B12 deficiency in total patients with T2D was 35% (54.5% in patients with gastroparesis and 11.1% in patients without gastroparesis). However, our findings are much higher than estimates from a study conducted by Amjad et al [ 32 ] where vitamin B12 deficiency was detected in 17.5% of patients with gastroparesis either diabetic or non-diabetic. The definition of vitamin B12 deficiency varies between studies; the cutoff point used in this study was 125 pmol/L which is comparable with Hansen et al [ 16 ] however, it is low compared with what is used in other studies [ 33 , 34 ].…”
Section: Discussioncontrasting
confidence: 89%
“…In the current study, the frequency of vitamin B12 deficiency in total patients with T2D was 35% (54.5% in patients with gastroparesis and 11.1% in patients without gastroparesis). However, our findings are much higher than estimates from a study conducted by Amjad et al [ 32 ] where vitamin B12 deficiency was detected in 17.5% of patients with gastroparesis either diabetic or non-diabetic. The definition of vitamin B12 deficiency varies between studies; the cutoff point used in this study was 125 pmol/L which is comparable with Hansen et al [ 16 ] however, it is low compared with what is used in other studies [ 33 , 34 ].…”
Section: Discussioncontrasting
confidence: 89%
“…This lack of caloric intake and associated physiological disturbances in the digestive tract [increased gastric pH because of proton pump inhibitors (PPI) treatment, bacterial overgrowth from decreased gastrointestinal motility and acidity, gastric operations/ vagotomy] also contribute to nutritional deficiencies. Amjad et al [5] reported micronutrient deficiencies (vitamin D, vitamin B12 and iron) in 49, 18, and 51%, respectively in their cohort of gastroparetic patients. Moreover, malnutrition status is related to higher mortality, in diabetic patients as well as in nondiabetic patients.…”
Section: Gastroparesis and Malnutritionmentioning
confidence: 96%
“…[97][98][99] These secondary complications of diabetes result from loss of interstitial cells of Cajal and neural abnormalities, which potentiate risk for malnutrition, diminished musculoskeletal reserve, and frailty. [100][101][102][103] A subjective global assessment based on features of the history and physical examination is considered a reliable bedside tool for diagnose of malnutrition and can identify those who would benefit from nutrition care, while also predicting outcomes. 104 A study using subjective global assessment in wait-listed SPK candidates showed that patients may have evidence of malnutrition despite normal body mass index (BMI).…”
Section: Pancreas Transplant Waitlist Outcomes and Surrogates Of Frailtymentioning
confidence: 99%
“…Patients with diabetes mellitus can have significant malnutrition related to a variety of gastrointestinal dysmotility disorders, such as gastroparesis, most commonly, but also slow intestinal transit, delayed colonic emptying, and constipation 97–99 . These secondary complications of diabetes result from loss of interstitial cells of Cajal and neural abnormalities, which potentiate risk for malnutrition, diminished musculoskeletal reserve, and frailty 100–103 …”
Section: Pancreas Transplant Waitlist Outcomes and Surrogates Of Frailtymentioning
confidence: 99%